تحليل العناصر الداخلية في فيلم الرسوم المتحركة كونغ فو باندا 2008 لأتان ريف وسيروس فوريس - Wijaya, Rivaldi Andi; Buska, Wahyudi (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
The purpose of this study was to determine the intrinsic elements (theme, plot, characters and characterizations, setting, point of view of the story) in the 2008 animated film Kung Fu Panda directed by Melissa Cobb, and to find out the values ​​contained in the animated film. The type of research used is qualitative research. The research data source is the animated film Kung Fu Panda 2008 in English and using Arabic translation by Shimaa Adel. The object of this research is the intrinsic elements in the 2008 animated film Kung Fu Panda published by the Layarkaca21.com website and the values ​​contained in the animated film. The method used to analyze the data is a description of the analysis. The results of the analysis of the intrinsic elements and values ​​contained in the 2008 film Kung Fu Panda. The theme contained in this film is struggle. The plot contained in this film is a mixed plot. The characters in this film are Poo, Tai Lung, Grand Master Oogway, Master Shifu, Tigress, Viper, Monkey, Mantis, Crane, Tuan Ping, Zeng, Commander Vachir. The setting in this film is a valley of peace. The point of view used in this film is in the first person, namely Po. The values ​​contained in this film are sincerity to achieve goals, patience over obstacles, suggestions to help each other.